Gender roles and masculinities in leveraging milk for household nutrition: Evidence from two districts in Rwanda - Farnworth, Cathy Rozel; Jumba, Humphrey; Otieno, P.E.; Galiè, Alessandra; Ouma, Emily A.; Flax, Valerie L.; Colverson, Kathleen E.; Schreiner, M.-A. (Elsevier, 2023)
Malnutrition in children remains a significant public health and development challenge in Rwanda. Animal Source Foods (ASFs) provide an important mechanism for supplying children with energy, proteins, and micro-nutrients. Using evidence from a study on the Girinka dairy program in Rwanda, this article adds a masculinities lens to nutrition strategies. It suggests potential ways to engage men in nutrition interventions whilst promoting gender-equitable masculinities that improve children’s access to ASFs and create more gender-equal relations.